The Role of Principal Leadership in Improving Educational Quality: Insights from Indonesia - Zulfahmi, Zulfahmi; Putra, Alhadi Yan; Fahmi, Muhammad (PPSDP International Journal of Education, 2025)
This study explores the leadership strategies adopted by the principal of SMAN 22 Palembang in enhancing educational quality. Employing a qualitative case study approach, data were collected through in-depth interviews with principals, teachers, and students. The findings reveal that a transformational leadership style marked by inspiration, empowerment, and innovation significantly improves teacher motivation and performance. Additionally, community support and adequate resources were found to be critical factors. This study underscores the importance of developing transformational competencies in school leadership and recommends targeted training programs and an environment conducive to continuous professional development.